Americium Inhalational Exposure with Successful Chelation Therapy. (17th October 2022) - Keenan, Michael; Behrens, Torsten; Bravenec, Stan; Davis, Jason; Bowen, Angie; Goans, Ronald; Iddins, Carol
Abstract: Americium is a man-made metal produced in very small quantities in nuclear reactors. Americium-241 is one of the radioactive isotopes of americium and has commercial applications, including use in smoke detectors. This is a case report of an occupational inhalation of americium-241, treated with both effective external decontamination and the use of diethylenetriamine pentaacetate to promote decorporation. This experience is significant because of the potential for americium or similar radionuclides to be used in "dirty" bombs or other radiological dispersion devices to cause large-scale radioactive contamination.